A prospective study to compare the efficacy of tacrolimus vs cyclosporine in vernal keratoconjunctivitis in children in India - Choudhary, Priya; Singh, Satya Prakash; Chaurasia, Rakesh Chandra; Jindal, Meenakshi (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Vernal keratoconjunctivitis (VKC) is a chronic allergic conjunctival disease. Immunomodulatory drugs like cyclosporine is being used for its treatment. Tacrolimus is another immunomodulator drug that can be used in VKC. This study was done to compare the efficacy of tacrolimus and cyclosporine in VKC. Methods: This prospective study was conducted on 60 patients of either sex by dividing them into two groups. The first group was treated with cyclosporine (0.05%) ophthalmic eye drop and second group with tacrolimus (0.03%) ophthalmic ointment. Total five objective signs (hyperaemia, oedema, papillae, corneal involvement and tantra’s dot) and five subjective symptoms (itching, tearing, foreign body sensation, discharge and photophobia) data was collected and tabulated for statistical analysis. Results: Authors found TSSS in both groups decrease significantly (p <0.05 or p <0.01 or p <0.001) at all post periods as compared to respective predecessor periods except 4 weeks to 6 weeks in cyclosporine group and 6 weeks to 8 weeks in tacrolimus group. Similarly, for each period, on comparing the mean TSSS between the groups TSSS between the groups at all periods does not differed statistically though at final evaluation (mean change from baseline to 8 weeks), it improved 5.2% more in tacrolimus group (83.7%) than cyclosporine group (78.5%). Similarly, TOSS also decreased at all post periods except 4 weeks to 6 weeks, and 6 weeks to 8 weeks in cyclosporine group and 6 weeks to 8 weeks in tacrolimus group. Improvement in scores was 11.6% more in tacrolimus (81.6%) than cyclosporine (70.0%). Cyclosporine eye drops are associated with burning sensation and redness of eyes while transient ocular irritation was only observed side effect with tacrolimus. Conclusions: The study found tacrolimus is clinically better drug for treatment of vernal keratoconjunctivitis than cyclosporine and is also cost effective.